A comparative analysis of face-to-face and online learning: evidence from accounting students at Universiti Teknologi MARA (UiTM), Perlis Branch - Abdullah, Azrul; Awang Ahmad @ Said, Nadzir; Mat Isa, Norshamshina; Saramas, Natcha (Universiti Teknologi MARA, Perlis, 2025)
For years, face-to-face learning has been at the heart of traditional education; however, advances in technology have transformed online learning into a widely embraced alternative. This study aims to evaluate the perceptions of accounting students at Universiti Teknologi MARA (UiTM), Perlis Branch towards face-to-face and online learning, and to compare academic performance between these two instructional methods. Data were collected through a structured questionnaire distributed among accounting students at UiTM Perlis. The findings reveal that students value the direct interaction provided by face-to-face learning, while also appreciating the flexibility offered by online learning. Although face-to-face learning appears more effective in enhancing academic performance, online learning offers significant advantages in terms of accessibility and flexibility. Based on these findings, this study recommends that UiTM Perlis, particularly the Faculty of Accountancy to consider adopting a more structured hybrid teaching model that integrates both learning methods to optimize student learning experiences and academic outcomes.